Toward the construction of educational practices grounded in the conceptual system of Cultural‑Historical Psychology - Konokotin, A.V.; Zaretsky, V.K.; Ulanovskaya, I.M.; Rubtsova, O.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The paper analyses how key concepts of cultural-historical psychology-zone of proximal development, joint activity, vraschivanie (the cultural grafting of individual action), pereghivanie, sign mediation, and reflection-can serve as design principles for effective educational practices and technologies. Three practices are examined in detail: the Reflexive-Activity Approach (RAA), which helps learners overcome academic difficulties and stimulates both cognitive and personal development; the diagnostic technique "Mosaic", devised to assess the formation of meta-disciplinary competences in primary-school children through the organisation of cooperative activity; and "Multimedia‑Theater", a qualitatively new form of organising adolescents' learning activity that, by means of systematically arranged role experimentation, fosters the central neoformations of this age period. The cases show how the core principles and propositions elaborated by L.S. Vygotsky-and later developed by his students and followers-can be effectively integrated into contemporary educational practice. В статье рассматривается применение фундаментальных понятий культурно-исторической психологии - зона ближайшего развития, совместная деятельность, вращивание, переживание, знаковое опосредствование, рефлексия, - для проектирования эффективных образовательных практик и технологий. Особое внимание уделяется таким практикам, как рефлексивно-деятельностный подход (РДП), направленный на оказание помощи учащимся в преодолении учебных трудностей и способствующий их когнитивному и личностному развитию; диагностическая методика «Мозаика», задачей которой выступает оценка сформированности метапредметных компетенций учащихся младшего школьного возраста в области организации совместной деятельности; «Мультимедиа-театр», позволяющий через специально организованный процесс ролевого экспериментирования формировать центральные новообразования подросткового возраста и являющийся одной из качественно новых форм организации учебной деятельности подростков. Представленные в статье практики наглядно демонстрируют, каким образом основополагающие принципы и положения культурно-исторической психологии, заложенные Л.С. Выготским и впоследствии развивавшиеся учениками и последователями его научной школы, могут быть эффективно интегрированы в образовательный процесс.